Development and characterization of sugar palm fiber-reinforced polymer composites for photovoltaic backsheet material - Abed, Alaaeddin M. H. (2019)
Natural fiber composites (NFCs) are reinforcing fibers extracted from biodegradable, renewable, and natural green resources. NFCs are employed in countless indoor and outdoor applications. This study introduces a new characterization and development of short sugar palm fiber (SSPF) reinforced polyvinylidene fluoride (PVDF) polymer, for photovoltaic (PV) applications. Due to the urgent need for efficient and resilient PV backsheets, this work characterizes new natural fiber composites to enhance durability, weatherability, efficiency, and functionality. A decision model was initially introduced to prioritize and determine the most appropriate polymer matrix type for SSPFs reinforced polymer composites. This process was accomplished using an integrated multi- criteria evaluation method based on three different methodologies: the analytic hierarchy process (AHP), technique for order of preference by similarity to ideal solution (TOPSIS), and the elimination and choice expressing reality (ELECTRE). A novel tripartite analysis was developed to display the aggregate evaluation of the three methods. PVDF was introduced as a potential polymer for composite preparation. Following fabrication, an in-depth investigation was accomplished to examine the mechanical, nanomechanical, physical, thermal, optical, and technical properties of PVDF-SSPF composites as potential alternatives for PV backsheets. The obtained results were verified for each testing process. The composites exhibited good mechanical and nanomechanical properties with outstanding tensile performance. Excellent physical and technical properties with extremely minor moisture content, water absorption, and thickness swelling were confirmed. More importantly, the composites possessed outstanding prolonged-testing results, displaying high stability when immersed in water and excellent thermal properties. They are suitable candidates for outdoor and PV applications. To gain further insight into the composites’ functional capabilities, they were fabricated as backsheets in the PV module. Other than the low cost of fabrication and its simplicity, the composites displayed adequate performance for solar cells such as thermal compatibility, good heat dissipation, durability, hardness, and excellent adaptation to the module. The developed module was simultaneously evaluated, electrical efficiency and I-V characteristics were evidenced achieving Pmax range of 19.23 W to 21.04 W and Imaxp range of 1.265 A to 1.394 A. The Vopen was between 19.59 V and 20.24 V. In the proportional analysis between PVDF-SSPF and the conventional backsheet; the PVDF-SSPF found to be less responsive to temperature and heat absorbance. The thermal start-end points were reported as (31.1°C, 45.7°C) and (32.0°C, 50.6°C) in both PVDF-SSPF backsheets and conventional backsheets; respectively. The total average variation between the two temperatures was 10.53°C. The module with PVDF-SSPF proved 8.54% decline in its temperature with excellent thermal shifts. The temperature shifts verified the improvement in thermal stability and the reduction in heat absorbance in PVDF-SSPF backsheet composites. Readings on the module’s performance provided further evidence of the composites’ high potential for being introduced as a unique solution for PV backsheet enhancements. Overall, characterization and development analyses were effectively accomplished. The PVDF-SSPF composites exhibited outstanding properties and can be essentially fabricated as backsheets where high durability, reliability, efficiency, weather- resistance, dielectric suitability, thermal stability, as well as optimal balance between such properties can be maintained. The study recommends that further efforts should be made to examine more relevant composites or other potential green materials to effectively contribute to the functionality of renewable energy systems. Additional research efforts should be made to investigate new opportunities for enhancing the bond between composites and PV solar modules with the use of suitable adhesives and laminating technologies. This will secure the continuous development, characterization enhancements, and proper utilization of these composites.